PENGARUH LEVEL TRANSPARANSI GOOD CORPORATE GOVERNANCE DAN KARAKTERISTIK DEWAN KOMISARIS TERHADAP NILAI PASAR PERUSAHAAN - Eman Sukanto; Maduretno Widowati (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2015)
This research aimed to analyze the effect of corporate governance transparancy level, crossdirectorship level and board of comisioner size on firm value manufacture company listed in Indonesian Stock Exchange 2014. Research methods by using multiple regression models. To test how much the dependent variable explained by the independent variables were able to determine the significance and influence of the independent variable on the dependent variable simultaneously using F test and partial test using the t test.Based on the test results indicate that corporate governance transparancy level effect on firm value (b1=0,261, t=3,287, p=0.001). Crossdirectorship level effect on firm value (b2=41,897, t=3,796, p=0.000). Board of comisioner size effect on firm value (b3=2,974, t=2,483, p=0.015).  Corporate governance transparancy level, Crossdirectorship level, and  board of comisioner size simultaneously affect on firm value. This is indicated by the value of F calculated from the test results is equal to 16,334 with the sig. F of 0.000 that is smaller than 5% significance level. Deteminant coefficient (R Square) of  0,293, which means that the effect of corporate governance transparancy level, crossdirectorship level and board of comisioner size on firm value amounted to 29,3% while the remaining 70,7% is influenced by other variables not included in the regression equation.